TOGAF ADM–Based Enterprise Architecture Design: A Design Science Study on Capability and Process Alignment in Digital Organizations - Hajar Dewantara; Andi Asrida Reskinah D; Nurul Aulia Fitriani; Risnawati S (Global Research and Collaboration, 2025)
TOGAF ADM (The Open Group Architecture Framework Architecture Development Method) is a structured and comprehensive framework for developing and managing PT Shopee Indonesia's architecture. TOGAF ADM provides a systematic approach to planning, designing, and implementing architectures that support business objectives. Within this framework, the architecture development process consists of a series of well-organized stages, from initial planning to implementation and maintenance of the architecture. Each TOGAF ADM stage is equipped with guidelines and templates that assist enterprise architects in describing, analyzing, and implementing architectural elements such as business architecture, data architecture, application architecture, and information technology architecture. Enterprise Architecture modeling using TOGAF ADM helps organizations understand the interrelated relationships between these architectural elements and ensure alignment with business strategy. By using TOGAF ADM, organizations can create and manage a consistent, integrated, and adaptive architecture, which helps in reducing complexity, increasing operational efficiency, and facilitating successful change and transformation. Understanding and applying TOGAF ADM provides practical guidance for enterprise architects in developing architectures capable of addressing complex business challenges and achieving competitive advantage.